Adaptive trait syndromes along multiple economic spectra define cold and warm adapted ecotypes in a widely distributed foundation tree species. (19th December 2020) - Blasini, Davis E.; Koepke, Dan F.; Grady, Kevin C.; Allan, Gerard J.; Gehring, Catherine A.; Whitham, Thomas G.; Cushman, Samuel A.; Hultine, Kevin R.
Abstract: The coordination of traits from individual organs to whole plants is under strong selection because of environmental constraints on resource acquisition and use. However, the tight coordination of traits may provide underlying mechanisms of how locally adapted plant populations can become maladapted because of climate change. To better understand local adaptation in intraspecific trait coordination, we studied trait variability in the widely distributed foundation tree species, Populus fremontii using a common garden near the mid‐elevational point of this species distribution. We examined 28 traits encompassing four spectra: phenology, leaf economic spectrum (LES), whole‐tree architecture (Corner's Rule) and wood economic spectrum (WES). Based on adaptive syndrome theory, we hypothesized that trait expression would be coordinated among and within trait spectra, reflecting local adaptation to either exposure to freeze‐thaw conditions in genotypes sourced from high‐elevation populations or exposure to extreme thermal stress in genotypes sourced from low‐elevation populations. High‐elevation genotypes expressed traits within the phenology and WES that limit frost exposure and tissue damage. Specifically, genotypes sourced from high elevations had later mean budburst, earlier mean budset, higher wood densities, higher bark fractions and smaller xylem vessels than their low‐elevation counterparts. Conversely, genotypes sourced from low elevations expressed traits within the LES that prioritized hydraulic efficiency and canopy thermal regulation to cope with extreme heat exposure, including 40% smaller leaf areas, 67% higher stomatal densities and 34% higher mean theoretical maximum stomatal conductance. Low‐elevation genotypes also expressed a lower stomatal control over leaf water potentials that subsequently dropped to pressures that could induce hydraulic failure. Synthesis . Our results suggest that Populus fremontii expresses a high degree of coordination across multiple trait spectra to adapt to local climate constraints on photosynthetic gas exchange, growth and survival. These results, therefore, increase our mechanistic understanding of local adaptation and the potential effects of climate change that in turn, improves our capacity to identify genotypes that are best suited for future restoration efforts. Abstract : Trait variability among Populus fremontii populations indicates there is a high degree of local adaptation to climate. The coordination of traits may provide underlying mechanisms of how locally adapted plant populations like P. fremontii along the Bill Williams river (LBWBIL) in western Arizona (pictured) can become maladapted because of climate change. Photo by Hillary Cooper, 2017.